49 A Quality Improvement Project to Assess and Refine the Handover Process at Morning Trauma Meetings. (4th May 2021) - Sadiq, S; Tahir, M; Nur, I; Elerian, S; Malik, A
Abstract: Introduction: Poor handover between shifts can result in patient harm. This study was designed to evaluate the impact of implementing a handover protocol on the quality of information exchanged in the trauma handover meetings in a UK hospital. Method: A prospective single-centre observational study was performed at an NHS Trust. Ten consecutive weekday trauma meetings, involving 43 patients, were observed to identify poor practices in handover. This data was used in conjunction with the Royal College of Surgeons' recommendations for effective handover (2007) to create and implement a standard operating protocol (SOP). Following its implementation, a further 8 consecutive meetings, involving a further 47 patients, were observed. The data was analysed using t-test for quantitative variables and chi-square or Fisher's exact tests for categorical variables. Results: An improvement was demonstrated in multiple aspects of trauma handover including past medical history, injury date, results, diagnosis, consent, mark, and starvation status (all p < 0.001). Subgroup analyses showed that handover of neck-of-femur fracture patients including information on baseline mobility (p = 0.04), Nottingham-Hip-Fracture Score (p = 0.01), next-of-kin discussion (p = 0.075) and resuscitation status (p = 0.001) all improved following the intervention. Conclusions: These results demonstrate that the implementation of a well-structured handover protocol can improve the transmission of critical information in trauma meetings.